Von Government zu Governance (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
This volume researches concepts of direct, participatory and deliberative democracy, their structures and procedures, and the role of actors. On the one hand, the volume focuses on questions of institutionalisation and the context sensitivity of participation-centred procedures in European federal and regional states. On the other hand, the volume addresses the question of the role that actors at the supranational level play or can play in the renewal of democratic processes. The state of research and its findings in theoretical and empirical democracy research provide the overarching conceptual framework for the volume. With contributions by Elisabeth Alber, Eva Maria Belser, Peter Bussjäger, Carmen Descamps, Annegret Eppler, Anna Gamper, Andreas Kiefer, Karl Kössler, Sabine Kropp, Olaf Leiße, Melanie Plangger, Julian Plottka, Wolf J. Schünemann, Christoph Schramek, Teija Tiilikainen, Jens Woelk and Carolin Zwilling.